The Application of GIS in Environmental Engineering: Opportunities and Limitations - Mohd Zuki, Nur Farah Aina; Mohamad Abdullah, Nazirah (Recent Trends in Civil Engineering and Built Environment, 2022)
Modern computer technology such as geographic information systems (GIS), assign cost-effective tools that can evaluate environmental outcomes to explore more comprehensively opportunities to apply GIS, particularly in environmental engineering. This research intends to conduct a systematic literature review on the advantages, constraints and explores significant issues related to the application of GIS in environmental engineering and interpreting 38 publish review papers through eligibility test. Major platforms such as Scopus and the Web of Science are used to identify the key issues associated with the application of GIS in environmental engineering. Precisely, the research presents and discusses the basic principles, potential benefits, and major limitations of GIS in environmental inquiry. Information acquired from main platforms and other platforms are also analyzed to produce graphs of GIS in environmental engineering, types of environmental engineering, benefits and limitations of GIS obtain from multiple articles. The expected result through GIS technology will come out with a systematic literature review that can proceed to play an essential role, offer significant added value to the system environment as well as gain a better understanding and local knowledge of GIS applications in the future.